2022
DOI: 10.1158/1541-7786.mcr-21-1010
|View full text |Cite
|
Sign up to set email alerts
|

EML4-ALK Variant 3 Promotes Mitotic Errors and Spindle Assembly Checkpoint Deficiency Leading to Increased Microtubule Poison Sensitivity

Abstract: EML4-ALK is an oncogenic fusion protein present in approximately 5% of non–small cell lung cancers (NSCLC). Alternative breakpoints in the gene encoding EML4 result in distinct variants that are linked to markedly different patient outcomes. Patients with EML4-ALK variant 3 (V3) respond poorly to ALK inhibitors and have lower survival rates compared with patients with other common variants, such as V1. Here, we use isogenic Beas-2B bronchial epithelial cell lines expressing EML4-ALK V1 or V3, as well as ALK-po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In contrast to v1, EML4-ALK v3 localizes to micro-tubules (5; 6) and might be associated, directly or indirectly, with other proteins involved in the formation of the mitotic spindle. For this reason and because of the high-confidence score of the SPDL1 gene in v3 H2228 cells, we further investigated the role played by depletion of Spindly in increasing the sensitivity of EML4-ALK v3 NSCLC cells to low concentrations of HSP90i.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast to v1, EML4-ALK v3 localizes to micro-tubules (5; 6) and might be associated, directly or indirectly, with other proteins involved in the formation of the mitotic spindle. For this reason and because of the high-confidence score of the SPDL1 gene in v3 H2228 cells, we further investigated the role played by depletion of Spindly in increasing the sensitivity of EML4-ALK v3 NSCLC cells to low concentrations of HSP90i.…”
Section: Resultsmentioning
confidence: 96%
“…We observed loss of cellular fitness upon combined depletion of Spindly and prolonged exposure to low concentrations of HSP90i exclusively in EML4-ALK v3, and not in v1, NSCLC cells. It has been shown that while both v1 and v3 localize to cytoplasmic granules, only v3 binds to microtubules (5; 6; 7). It is tempting to speculate that v3 may bring the tyrosine kinase activity of ALK to the spindle where the phosphorylation of proteins involved in chromosome congression might generate a specific vulnerability to loss of Spindly and to prolonged treatment with low concentrations of HSP90i.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they found that the EML4-ALK V3 protein localised to the mitotic spindle microtubules with cells exhibiting stabilized K-fibres and increased mitotic defects including multipolar spindles, lagging chromosomes in metaphase and misaligned chromosomes in anaphase compared to cells expressing V1. Finally, the activity of the spindle assembly checkpoint was found to be reduced in cells expressing V3 compared to V1 [ 109 ]. Taken together, these two studies demonstrate the potential of combining ALK TKIs with microtubule poisons or targeted mitotic agents as an alternative to ALK inhibitor monotherapy ( Figure 5 ).…”
Section: Combination Of Alk Inhibitors and Chemotherapymentioning
confidence: 99%
“…Microtubule poisons have been regularly used as chemotherapies for many tumour types, including One example is vincristine, a vinca alkaloid chemotherapy that promotes microtubule depolymerization by binding to tubulin monomers [107]. Sampson et al (2022) sought to test the benefit of combining vincristine with ALK inhibitors in EML4-ALK patient-derived cells. They found that the combination of vincristine together with crizotinib or ceritinib led to an increased loss of cell viability and enhanced apoptosis in cells expressing V1, but not V3 [108].…”
Section: Combination Of Alk Inhibitors and Chemotherapymentioning
confidence: 99%